Skin Anti-Aging Properties of the Glycopeptide- and Glycoprotein-Enriched Fraction from a Cosmetic Variation of the Longevity Medicine, Gongjin-Dan - Gwang Jin Lee; Jiwon Park; Hyeon Jun Jeon; Tae Heon Kim; Hyejin Lee; Seongsu Kang; Seung Jin Hwang; Nam Seo Son; Nae-Gyu Kang (Cosmetics, 2025)
This study deals with the extraction of active compounds for a formula (Angelica gigas, Cornus officinalis, Ganoderma lucidum, Thymus vulgaris, and Asparagus cochinchinensis) and the evaluation of its skin anti-aging properties. This formulation was inspired by the oriental medicine Gongjin-dan (Angelica gigas, Cornus officinalis, deer antler, and musk), which has been used as a restorative drug for longevity. Enzyme-based extraction and chemical purification were used to obtain a mixed fraction (GEF) enriched in glycopeptides and glycoproteins from the five herbal materials. The chemical characteristics of GEF, including the carbohydrate groups attached to the peptides and proteins, the total carbohydrate and protein contents, and the composition of monosaccharides and amino acids were determined. The chemical characteristics that were significantly different from those of the extract, generally prepared in the same ratio, were the abundance of glycopeptides and glycoproteins and the high proportions of conditionally essential amino acids (51.0%) and acidic/basic amino acids (67.7%). These are necessary components for strengthening the skin layers against aging. The in vitro skin anti-aging properties of GEF on human fibroblasts (HS68), keratinocytes (HaCaT), and adipose-derived mesenchymal stem cells (ADMSCs) were evaluated. It was found that MMP-1 gene expression was inhibited (18–28%) and fibrillin-1 protein (23–37%) was restored contrary to the effect of UV irradiation. COL1A1 and COL4A1 gene expression (25–35%), HAS2 gene expression (22–213%), and adipogenesis (15%) were facilitated. These results demonstrate the potential of GEF as a raw material for skin anti-aging and reinforce the scientific evidence supporting a traditional medicine with a long history.